Pengaruh Program Corporate Social Responsibility (CSR) terhadap Customer Engagement dengan Brand Image sebagai Variabel Mediasi pada Customer PT Indolakto Purwosari Pasuruan - Hasanah, Roudhotul; Murtadlo, Kholid (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2025)
This study aims to analyze the effect of Corporate Social Responsibility (CSR) programs on Customer engagement with Brand Image as a mediating variable among customers of PT Indolakto PurwosariPasuruan. The research employs a quantitative method using a survey approach with purposive sampling involving 96 respondents who are assumed to know and understand the CSR programimplemented by the company. Respondents knowledge was measured through a questionnaire assessing their awareness, understanding, and perception of the content, goals, and benefits of CSRprograms. Data analysis was conducted using Path Analysis and Sobel mediation tests. The results show a positive and significant impact of CSR programs on both Brand Image and Customerengagement. Brand Image also significantly mediates the relationship between CSR and Customer engagement. This indicates that an effective CSR program not only strengthens Brand Image but alsoenhances customer engagement emotionally and actively. The study recommends that companies improve the implementation and communication of CSR programs to strengthen customer loyalty andlong-term relationships.